2018
DOI: 10.1101/248302
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metatranscriptome analysis of the vaginal microbiota reveals potential mechanisms for protection against metronidazole in bacterial vaginosis

Abstract: Bacterial vaginosis (BV) is a prevalent multifactorial disease of women in their reproductive years characterized by a shift from the Lactobacillus spp. dominated microbial community towards a taxonomically diverse anaerobic community. For unknown reasons, some women do not respond to therapy. In our recent clinical study, out of 37 women diagnosed with BV, 31 were successfully treated with metronidazole, while 6 still had BV after treatment. To discover possible reasons for the lack of response in those patie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…Populations of bacterial species in vaginal communities are likely comprised of multiple strains. Previous studies of the vaginal microbiome have largely treated these species as singular genotypes 43 , although some more recent studies have examined intraspecies diversity in these communities 44,45 . Intraspecies diversity is important because it is likely to influence many properties of the communities including their temporal stability and resilience, as well as how they relate to host health.…”
Section: Discussionmentioning
confidence: 99%
“…Populations of bacterial species in vaginal communities are likely comprised of multiple strains. Previous studies of the vaginal microbiome have largely treated these species as singular genotypes 43 , although some more recent studies have examined intraspecies diversity in these communities 44,45 . Intraspecies diversity is important because it is likely to influence many properties of the communities including their temporal stability and resilience, as well as how they relate to host health.…”
Section: Discussionmentioning
confidence: 99%
“…Complementary ‐omic technologies aimed at evaluating the functional capacity of the microbiome, including metatranscriptomics and metaproteomics, offer further opportunities to expand our understanding of gene transcriptional activity and protein expression respectively in complex microbial communities inhabiting the human body. To date, metatranscriptomics with RNA‐seq has only been exploited in a handful of small studies of the vaginal microbiome . Vaginal bacterial metatranscriptome comparison between two women with BV and two healthy individuals indicated that in BV, L. iners increases transcription of cholesterol‐dependent cytolysin, genes involved in glycerol metabolism, and CRISPR‐related genes .…”
Section: Introductionmentioning
confidence: 99%
“…Vaginal bacterial metatranscriptome comparison between two women with BV and two healthy individuals indicated that in BV, L. iners increases transcription of cholesterol‐dependent cytolysin, genes involved in glycerol metabolism, and CRISPR‐related genes . Comparing the vaginal bacterial metatranscriptome in BV between metronidazole treatment responders and non‐responders, found that increased transcription of CRISPR‐Cas genes in G. vaginalis in non‐responders may mitigate treatment resistance . Metatranscriptomic analyses of cultured vaginal bacteria under different growth conditions may also provide important information.…”
Section: Introductionmentioning
confidence: 99%
“…RNA from expressed genes is stronger evidence for functional activity than DNA, as many genes are only conditionally expressed. However, metatranscriptomic sequencing may not capture all species in the vaginal microbiome if some are insufficiently active at the time of sampling . Thus metatranscriptomic sequencing provides a census of who‐is‐active, rather than who‐is‐there, and an inventory of their transcriptionally active genes and pathways.…”
Section: Community Sequencing Methodsmentioning
confidence: 99%
“…Community sequencing is furthering the study of how BV‐associated microbes increase HIV and HPV risk and reduce efficacy of antiretrovirals for HIV prevention . Metatranscriptomic sequencing of the vaginal microbiome during BV and STI is being used to find pathways related to aetiology, treatment targets, and treatment evasion, as well as to determine the dominant pathogen in STI co‐infection …”
Section: Research In the Vaginal Microbiome Using Community Sequencingmentioning
confidence: 99%